"German Culture is where I am": Thomas Mann in Exile - Helmut Koopmann (Studies in 20th & 21st Century Literature, 1982)
Thomas Mann in exile reacted like many writers expelled from Germany: totally irritated he tried to defend his own identity by claiming that he was still the leading representative of Germany. But about 1938 a process of dissociation from Germany started which led to sharp remarks on Germany in his The Beloved Returns, to his conviction that German culture was where he lived and to the acknowledgement of America as his new home. Traces of his experience of exile, and a late answer on his separation from Germany in 1933, however, are to be found even in his incompleted novel Felix Krull which seems to have turned the disgusting experience of exile into friendly mythological light.
Keywords: Thomas Mann; exile; Germany; identity; dissociation; German; The Beloved Returns; culture; German culture; America; new home; experience of exile; Felix Krull